"Scoping" the Routes, Roots, and Rights to the City: "Mobilities of Vision" and Reading the Social Movement Landscape of Thessaloniki, Greece. Issue 2 (2nd July 2020) - Baker, James E.; Clancy, Kelly A.
Abstract : This paper uses a novel qualitative visual methodology—scoping—to interrogate the Lefebvrian right to the city across the social movement landscape of Thessaloniki, Greece. Generating a reflexive and experimental visual field practice, we narrativize photographs and field notes taken in central Thessaloniki in May, 2018, where we intervene in touristic scopic regimes as family-tourists-researchers, negotiating spaces where claims to roots, routes, and rights to the city are performed. We consider the placemaking tactics of a solidarity march for LGBTQI refugees in Thessaloniki and appropriations of public space for "simultaneity and encounter" through autogestion, followed by a nationalist Pontic Greek rally which put the mayor of Thessaloniki in hospital and into global media discourse. Our methods of "picturing power" seek to reimagine Lefebvre's "right to the city" by offering an account of the knitting together of subjects, materials, and traces which enact kinetic and multivocal revelations of activist politics in urban space.